Membrane-Enriched Proteomics Link Ribosome Accumulation and Proteome Reprogramming With Cold Acclimation in Barley Root Meristems - Martinez-Seidel, Federico; Suwanchaikasem, Pipob; Nie, Shuai; Leeming, Michael G.; Pereira Firmino, Alexandre Augusto; Williamson, Nicholas A.; Kopka, Joachim; Roessner, Ute; Boughton, Berin A. (Frontiers in Plant Science, 2021)
Due to their sessile nature, plants rely on root systems to mediate many biotic and abiotic cues. To overcome these challenges, the root proteome is shaped to specific responses. Proteome-wide reprogramming events are magnified in meristems due to their active protein production. Using meristems as a test system, here we study the major rewiring that plants undergo during cold acclimation. We performed tandem mass tag-based bottom-up quantitative proteomics of two consecutive segments of barley seminal root apexes subjected to suboptimal temperatures. After comparing changes in total and ribosomal protein fraction-enriched contents with shifts in individual protein abundances, we report ribosome accumulation accompanied by an intricate translational reprogramming in the distal apex zone. Reprogramming ranges from increases in ribosome biogenesis to protein folding factors and suggests roles for cold-specific ribosomal protein (RP) paralogs. Ribosome biogenesis is the largest cellular investment, thus, the vast accumulation of ribosomes and specific translation related proteins during cold acclimation could imply a divergent ribosomal population that would lead to a proteome shift across the root. Consequently, beyond the translational reprogramming, we report a proteome rewiring. First, triggered protein accumulation includes spliceosome activity in the root tip and a ubiquitous upregulation of glutathione production and S-glutathionylation (S-GSH) assemblage machineries in both root zones. Secondly, triggered protein depletion includes intrinsically enriched proteins in the tip-adjacent zone, which comprise the plant immune system. In summary, ribosome and translation related protein accumulation happens concomitantly to a proteome reprogramming in barley root meristems during cold acclimation. The cold accumulated proteome is functionally implicated in feedbacking transcript to protein translation at both ends and could guide cold acclimation.